Analisis Pengelolaan Transportasi Tempat Pembuangan Sampah (TPS) Merjosari di Kecamatan Lowokwaru Kota Malang - Lopes , Yulianus Sequira; Yurnalisdel, Yurnalisdel; Sulistyani , Kiki Frida (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2023)
The participation of stakeholders and the community plays an important role in waste management. Merjosari Park is a beautiful park located close to residential areas, making it one of the most profitable locations in Lowokwaru District. The purpose of this study is to determine the population and waste generation at the Merjosari Village TPS, analyze the TPS and the way waste is transported at the Merjosari District TPS, and determine the transportation link between the TPS and the Supit Urang Landfill. Several conclusions can be drawn from the analysis of the population in Merjosari Subdistrict in 2024 which amounted to 23,085 people and in 2028 increased to 27,005 people based on calculations and planning studies that have been carried out. In Merjosari Village, waste production is estimated to reach 4,432,089 tons per year in 2024 and 5,184,690 tons per year in 2028. Based on the results of the TPS analysis, Merjosari Village requires ten units of fiber bins with a capacity of 0.66 m3, three motorized carts with a capacity of 1.5 m3 for collection, and a compactor fleet with a capacity of 10 m3 per compactor unit for waste transportation in 2024. Twelve fiber bins with a capacity of 0.66 m3 will be available by 2028. Three motorized carts, or 1.5 m3 collection equipment, will be available for use, and one compactor, or 10 m3 capacity, will be used for waste transportation. Tracking of transportation from TPS to landfill shows an average trip time of 4.25 hours per minute.